2022
DOI: 10.1177/00420859221097884
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the “Dual Pandemics”: The Cumulative Impact of the COVID-19 Pandemic and Rise in Awareness of Racial Injustices among High School Students of Color in Urban Schools

Abstract: We explored the psychological and educational impact of distance learning during the COVID-19 and racial injustice pandemics. The sample included 19 urban high school students of Color from the San Francisco Bay Area. Interview data were analyzed using Reflexive Thematic Analysis revealing seven themes: (1) challenges learning from home; (2) shifts that impact students’ experience with school; (3) emotions emerging from the COVID-19 pandemic; (4) increased awareness and engagement related to racial injustices;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Black emerging adults also experienced a double pandemic in 2020 – the COVID-19 pandemic and a racism pandemic (Addo, 2020). More specifically, pandemic challenges were exacerbated by the murders of George Floyd, Breonna Taylor, and too many other individuals who identity as Black, and after which protests emerged through the Black Live Movement to address systemic racism in policing (Yeh et al, 2022). Similarly, to other emerging adults (Wardell et al, 2020), Black Americans may have used alcohol to self-medicate and cope during these challenging times (Shield et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Black emerging adults also experienced a double pandemic in 2020 – the COVID-19 pandemic and a racism pandemic (Addo, 2020). More specifically, pandemic challenges were exacerbated by the murders of George Floyd, Breonna Taylor, and too many other individuals who identity as Black, and after which protests emerged through the Black Live Movement to address systemic racism in policing (Yeh et al, 2022). Similarly, to other emerging adults (Wardell et al, 2020), Black Americans may have used alcohol to self-medicate and cope during these challenging times (Shield et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to concerns about the prevalent health issues (Gorey and Vena, 1995), including obesity, cancer and depression, healthcare research increasingly focuses on specific demographics, such as urban students of color (Yeh et al, 2022), Latin-American families (Mendez et al, 2021), marginalized individuals (Shedlin et al, 2006), and families with special needs (Shedlin et al, 2006), in the bay areas located in the United States. However, the majority of healthcare research primarily focuses on disease treatment and technical support to disadvantaged populations to enhance access to healthcare services (Xia et al, 2019;Mendez et al, 2021), but issues related to healthcare policies receive limited attention and few studies indicated the reduced viability of finance and human capital for providing these services.…”
Section: Healthcarementioning
confidence: 99%
“…Moreover, growing numbers of publications in the Greater Bay Area are focusing more on education, as the sustainable policy strategies view education as social capital for young people to pursue a better life and social mobility (Tang, 2020;Liu, 2021;Xie et al, 2021;Baur, 2022;Mok, 2022;Zhu and Mok, 2022). With the influence of the transition in lifestyle on remote working and learning during the COVID-19 pandemic (Connolly et al, 2021;Yeh et al, 2022), it is crucial to consider whether the functions of the bay areas as an urban agglomeration of labor and consumer groups have to shift their focus from the development of materialistic infrastructure to the provision of extensive social services, such as quality education for underprivileged individuals. Additionally, as the literature noted, edge cities are expanding in most bay areas, demanding extra state assistance to maintain respectable living conditions for the residents who are left behind by the center cities.…”
Section: Policy Implementation and Recommendationsmentioning
confidence: 99%
“…For example, the deaths of George Floyd and Breonna Taylor, among others, prompted a new wave of the Black Lives Matter (BLM) movement, highlighting the ongoing issues of systemic oppression and structural racism faced by Black communities and minoritized populations broadly. These events have also brought increased attention to social injustice and civic engagement among Black youth and other youth of color (Baskin‐Sommers et al, 2021; Yeh et al, 2022). Additionally, the pandemic exacerbated the country's preexisting anti‐immigration and exclusionary policies, disproportionately affecting youth from immigrant and Latinx families (Valdez et al, 2023).…”
Section: Family and Peer Ethnic‐racial Support In Adolescents' Everyd...mentioning
confidence: 99%
“…For example, according to recent national data, Black adolescents and those from other ethnic‐racial minority groups have been highly engaged in the BLM movement during the pandemic, especially in online spaces (Baskin‐Sommers et al, 2021). Qualitative interviews show that youth from various ethnic‐racial minority groups are inspired by their friends' and peers' involvement in this movement; they have also engaged in conversations with friends on topics of racism, oppression, and justice during this time (Fine et al, 2021; Yeh et al, 2022). Informed by this work, the current study tested the competing hypotheses regarding how peer ethnic‐racial support has changed from before to during the pandemic on a daily basis.…”
Section: Family and Peer Ethnic‐racial Support In Adolescents' Everyd...mentioning
confidence: 99%